Emerging roles for human glycolipid transfer protein superfamily members in the regulation of autophagy, inflammation, and cell death. (April 2020) - Mishra, Shrawan K.; Gao, Yong-Guang; Zou, Xianqiong; Stephenson, Daniel J.; Malinina, Lucy; Hinchcliffe, Edward H.; Chalfant, Charles E.; Brown, Rhoderick E.
Abstract: Glycolipid transfer proteins (GLTPs) were first identified over three decades ago as 24kDa, soluble, amphitropic proteins that specifically accelerate the intermembrane transfer of glycolipids. Upon discovery that GLTPs use a unique, all-α-helical, two-layer 'sandwich' architecture (GLTP-fold) to bind glycosphingolipids (GSLs), a new protein superfamily was born. Structure/function studies have provided exquisite insights defining features responsible for lipid headgroup selectivity and hydrophobic 'pocket' adaptability for accommodating hydrocarbon chains of differing length and unsaturation. In humans, evolutionarily-modified GLTP-folds have been identified with altered sphingolipid specificity, e. g. ceramide-1-phosphate transfer protein (CPTP), phosphatidylinositol 4-phosphate adaptor protein-2 (FAPP2) which harbors a GLTP-domain and GLTPD2. Despite the wealth of structural data (>40 Protein Data Bank deposits), insights into the in vivo functional roles of GLTP superfamily members have emerged slowly. In this review, recent advances are presented and discussed implicating human GLTP superfamily members as important regulators of: i ) pro-inflammatory eicosanoid production associated with Group-IV cytoplasmic phospholipase A2 ; ii ) autophagy and inflammasome assembly that drive surveillance cell release of interleukin-1β and interleukin-18 inflammatory cytokines; iii ) cell cycle arrest and necroptosis induction in certain colon cancer cell lines. The effects exerted by GLTP superfamily members appear linked to their ability to regulate sphingolipid homeostasis by acting in either transporter and/or sensor capacities. These timely findings are opening new avenues for future cross-disciplinary, translational medical research involving GLTP-fold proteins in human health and disease. Such avenues include targeted regulation of specific GLTP superfamily members to alter sphingolipid levels as a therapeutic means for combating viral infection, neurodegenerative conditions and circumventing chemo-resistance during cancer treatment.